Особливості сенсорно-пізнавального розвитку дітей п’ятого року життя в предметно-практичній діяльності - Медвідь, Наталія Юріївна (My University, 2023)
Кваліфікаційну роботу присвячено аналізу проблеми сенсорно-пізнавального розвитку дітей п’ятого року життя. Роботу виконано на теоретичному та практичному рівнях. На теоретичному рівні обгрунтовано актуальність теми дослідження, розроблено концептуальні підходи до його організації, визначено особливості його прояву у предметній діяльності, визначено педагогічні умови оптимізації виховного процесу у закладі дошкільної освіти. На практичному рівні розкрито критерії, показники та компоненти сен сорно-пізнавального розвитку, визначено рівні його сформованості розроблено методичні рекомендації для вихователів закладів дошкільної освіти з метою покращання показників сенсорно-пізнавального розвитку дітей п’ятого року життя в предметно-практичній діяльності.
The qualification work is devoted to the analysis of arbitrariness as the ability of a child of younger preschool age to consciously regulate behavior, to obey certain rules and to achieve the set goal of subject-practical activity. The relationship between elementary forms of self-regulation of behavior and personal growth of children in the fourth year of life is revealed. The criteria for assessing the levels of formation in the early ontogenesis of voluntary behavior were determined and the indicators of each criterion were characterized. Pedagogical conditions for the effective formation of voluntary behavior in a growing personality are theoretically substantiated, it is emphasized that the key point in the optimization of the educational process in special education is the laying of the foundations for the formation and development of the subject position created for this purpose in the developmental environment. Key words: personality development, arbitrary behavior, self-regulation mechanism, new formation of consciousness and personality, indicators of arbitrariness assessment, conditions for optimizing the educational process
Keywords: пізнання; сенсорний розвиток; сенсорно-пізнавальне виховання; комплексна методика